Review of Islamic Law on the Practice of Early Marriage in Limpakuwus Village, Sumbang, Banyumas - Aji, Imam Purnomo (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
Early marriage is still a problem in Limpakuwus Village, Sumbang, Banyumas, especially with 9 couples out of a total of 38 who are married. This village has a belief that getting married before the age of 20 is considered taboo or